Pemantauan Penggunaan Media Sosial Twitter Menggunakan Social Network Analysis dalam Melihat Politik Programatik pada Kampanye Pilkada Kota Depok Tahun 2020 - Wildhan Khalyubi; Christian Deswinta Bangun; Muhammad Rifqi Romadhona; Fikri Ardiyansyah (Badan Pengawas Pemilihan Umum, 2021)
This research aims to explain the observation result of social media Twitter utilization on programmatic politics campaign in each candidate pairs as the winning attempt on 2020 regional head election in Depok City. Two candidate pairs are contesting on 2020 regional head election in Depok City. The number 1 candidate pair is Pradi Supriatna and Afifah Alia, carried by The Coalition of Depok Rises. Meanwhile, candidate pair number 2 is Mohammad Idris and Imam Budi Hartono, carried by the Coalition of the Ordered, Fair, and Prosperous. This research is qualitative research on a campaign about the campaign activities which viewed through the programmatic politics campaign of each candidate pair's Twitter account. The data collection technique in this research uses Social Network Analysis (SNA) on Twitter accounts that represent each candidate pair. Those accounts are such as @pradi_afifah and @idrisimam2020. This research also integrates Andreas Jungherr’s perception of social media function on the campaign and Bardhan & Mookherjee’s perception of programmatic politics. Both perceptions intended to look social media function on doing programmatic politics campaign each candidate pairs. The findings of this research are that each candidate pairs enable social media Twitter as a programmatic politics campaign that offers the policy of various problems in Depok City.